Professional Nurse Traineeship. - Beatty, Ellen (1988)
Keywords: dept.nur; faculty_collection; sabbatical_report

Community Health Nursing. - Milone-Nuzzo, Paula (1988)
Keywords: dept.nur; faculty_collection; sabbatical_report

High-technology and hospice home care. Strange bedfellows - Hays, J.C. (Nursing Clinics of North America, 1988)
Technologic advances are changing hospice home care. A case study explores the clinical dilemmas and illustrates the educational and research agendas required to resolve them.
Keywords: Adult; Case Report; Female; Home Care Services; Hospices; Human; Patient Care Planning; Patient Care Team; Technology; High-Cost; Terminal Care; United States; computer analysis; dept.nur; home care; hospice; medical technology; organization and management; review; technical aid; united states; ⛔ No DOI found